2007
DOI: 10.1038/sj.ijir.3901599
|View full text |Cite
|
Sign up to set email alerts
|

Management of penile fractures complicated by urethral rupture

Abstract: The combination of lesions of the penile urethra and the corpus cavernosum is rare and likely to go unremarked. It worsens the immediate and long-term prognosis and poses a problem of management. Among 312 cases of penile fracture, we performed a retrospective study of a series of 10-case of traumatic corpora cavernosa rupture complicated with urethral rupture, treated in the department of Urology at 'Charles Nicolle' Hospital in Tunis. The median patients' age was 30 years. The most common mechanism was manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 16 publications
4
56
0
Order By: Relevance
“…6 Zaargoshi, however, showed an incidence of urethral lesion with corpora cavernosa fracture of 38% and the absence of these features did not exclude the possibility of urethral involvement. 9 Another study reported on 15 patients who underwent immediate surgical exploration; 4 of these had urethral injuries with no complications at 7.5 month follow-up.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…6 Zaargoshi, however, showed an incidence of urethral lesion with corpora cavernosa fracture of 38% and the absence of these features did not exclude the possibility of urethral involvement. 9 Another study reported on 15 patients who underwent immediate surgical exploration; 4 of these had urethral injuries with no complications at 7.5 month follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…Penile ultrasound can be used to assist the diagnosis of penile fracture; it can be easily performed, is non-invasive and useful in determining localized sub-Buck's fascia hematoma due to injury or to causes other than tunical tear. 6 Also magnetic resonance (MR) imaging is potentially useful to assess the penile rupture; the key finding is disruption of the low-signal intensity tunica albuginea, which is well-seen on both T1 and T2 weighted images, although T1 weighted sequences may detect more subtle fractures. 7 Treatment may be either conservative or immediate surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is underreported, and the true incidence is unknown, although an extensive review by Eke in 2001 reported 1331 cases identified in literature from 1966 to 2001 (Redman & Miedema, 1981;Eke, 2002;Derouiche et al, 2008;Al-Shaiji et al, 2009). Injury is defined as traumatic rupture of the tunica albuginea of one or both of the corpora cavernosa, occurring most often in the young adult (Morey & Dugi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fracture can extend to involve the corpus spongiosum and urethra. Previously thought to be a rare complication of penile fracture, urethral injury has been associated with between 10 and 38% of all penile fractures in the United States and Europe (Cendron et al, 1990;Tsang & Demby, 1992;Gottenger & Wagner, 2000;Derouiche et al, 2008;Al-Shaiji et al, 2009). In the Middle East, urethral injury is far less common, occurring in 0-3% of fractures (Zargooshi, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation